Dogsong eaudiobook - Paulsen, Gary (Recorded Books Inc., 2007)
Gary Paulsen's Dogsong-a Newbery Honor Book and an ALA Best Book for Young Adults-is the graphic, coming-of-age tale of a modern Eskimo lad and his consuming vision quest and harrowing struggle for survival. Troubled by changes in his Alaskan village, 14-year-old Russell Suskitt seeks the counsel of the village elder-and only dog team owner. After his training in the ancient arts of hunting with bow and lance, handling sled dogs, and surviving arctic dangers, Russell embarks upon his lonely search for Eskimo manhood. "Unusual and moving . a remarkable book."-Library Journal, starred review